2019
DOI: 10.37134/jcit.vol9.8.2019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Malaysian E-Commerce Taxation: A Qualitative Insight of Online Businesses

Abstract: Electronic commerce (e-commerce) is mushrooming in today's digital world across continents. However, this phenomenon seems not reflective of the tax collected, especially from consumer-to-consumer (C2C) online business transactions. Considering this issue, this paper focuses on the area of C2C business transactions. Our aims are to determine the level of understanding of e-commerce taxation of the students who involved in online businesses during their study years, and to gauge their attitude towards implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…On the contrary, some taxpayers might have been exercising better tax planning in terms of tax avoidance if they have higher degree of tax knowledge (Bornman & Ramutumbu, 2018). However, in reference to a forementioned studies which indicate a significant relationship between tax knowledge and compliance behaviour were not consistent with a studies by Yeo, Lim & Azhar, (2019) and Newman, Charity & Ongayi, (2018). Particularly, they claimed that tax knowledge has no significant influence on taxpayers' compliance behaviour and thus knowledgeable taxpayers are not necessarily compliant.…”
Section: Tax Knowledgementioning
confidence: 86%
See 1 more Smart Citation
“…On the contrary, some taxpayers might have been exercising better tax planning in terms of tax avoidance if they have higher degree of tax knowledge (Bornman & Ramutumbu, 2018). However, in reference to a forementioned studies which indicate a significant relationship between tax knowledge and compliance behaviour were not consistent with a studies by Yeo, Lim & Azhar, (2019) and Newman, Charity & Ongayi, (2018). Particularly, they claimed that tax knowledge has no significant influence on taxpayers' compliance behaviour and thus knowledgeable taxpayers are not necessarily compliant.…”
Section: Tax Knowledgementioning
confidence: 86%
“…Therefore, there is a high probability that they were not reporting cash in hand transactions and disclosing lesser revenue than they earned. Previous studies have also found that there are still many small business taxpayers with online businesses do not submit their tax returns, yet they may generate extra income without paying taxes (Yeo, Lim & Azhar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Enachescu et al (2019), for example, utilised experimental mixed-method surveys to look into how tax decisions affect people's emotions. A few studies, such as Onu and Oats (2018), and Yeo et al (2019), were qualitative in nature. Their studies have uncovered hidden issues in tax compliance, particularly the reason why people intend not to comply with the tax regulations.…”
Section: Analysis Of Of the Methodologymentioning
confidence: 99%
“…Besides, journal.ump.edu.my/ijim ◄ research on individual taxpayers has been done in Indonesia and Barbados by Andreas and Savitri (2015) and Alleyne and Harris (2017), respectively. Tax compliance intention issues have been studied in Malaysia (Shaharuddin et al, 2012;Palil & Rusyidi, 2013;Mohdali & Pope, 2014;Al-Mamun et al, 2014;Tallaha et al, 2014;Hassan et al, 2016;Mohamad et al, 2017;Sapiei et al 2017, & Yeo et al, 2019. The studies' discussions were from the perspectives of individual taxpayers, small business entrepreneurs, and students.…”
Section: Analysis Of the Theories Usedmentioning
confidence: 99%
“…Cabe mencionar que la educación en contabilidad y tributación es fundamental para las empresas comerciales en el Ecuador ya que les ayuda a cumplir con sus obligaciones tributarias y contables y a tomar decisiones informadas y estratégicas en base a su situación financiera (Yeo et al, 2019). En el país, las empresas comerciales están sujetas a una variedad de leyes y reglamentos contables y fiscales.…”
Section: Introductionunclassified